NYERI PERUT BERULANG SAAT HAID, BERISIKO MANDUL? - Mohd Andalas; Cut Rika Maharani; Rayhan Shafithri (Universitas Syiah Kuala, 2019)
Abstract. Stomach pain (dysmenorrhea) is abdominal cramps and pain during the menstrual period which can interfere with the daily activities of women of reproductive age. Dysmenorrhea is one of the symptoms that needs to be considered because it is often experienced by women and is an early sign of suffering from endometriosis. The presence of abdominal pain in women during menstruation, accompanied by pelvic pain, and infertility is a classic trias of symptoms used to diagnose endometriosis. Endometriosis occurs in almost 10% of women in the reproductive age period and more than 25-40% in infertile women. The risk of infertility is also linked because inflamed endometriosis tissue damages sperm and egg cells. Some treatments that can be done for patients with endometriosis are medical and surgical therapy. If medical therapy fails, operative laparoscopy can be alternative and hysterectomy can be considered for patients who no longer expect their reproductive function. Keywords: abdominal pain, endometriosis, infertility, dysmenorrhea. Abstrak. Nyeri Perut (dismenore) merupakan kram perut dan nyeri selama periode menstruasi yang dapat mengganggu aktivitas sehari-hari wanita usia reproduksi. Dismenore merupakan salah satu gejala yang perlu dipertimbangkan karena kerap dialami wanita dan menjadi tanda awal menderita endometriosis. Adanya nyeri perut pada wanita saat haid, disertai nyeri panggul, dan infertilitas merupakan trias klasik gejala yang digunakan untuk mendiagnosis endometriosis. Endometriosis terjadi pada hampir 10% wanita dalam kurun usia reproduksi dan lebih dari 25-40% pada wanita infertil (mandul). Risiko mandul juga dikaitkan karena jaringan endometriosis yang meradang merusak sperma dan sel telur. Beberapa pengobatan yang dapat dilakukan pada penderita endometriosis adalah terapi medikamentosa dan pembedahan. Jika terapi medikamentosa gagal, laparoskopi operatif dapat menjadi altenatif dan histerektomi dapat dipertimbangkan pada pasien yang tidak mengharapkan fungsi reproduksi lagi. Kata Kunci: nyeri perut, endometriosis, infertilitas, dismenore.